South Atlantic fault-lines: Maritime security dynamics between Brazil and the EU - Seabra, Pedro (Europe, Maritime Security and Small Navies Conference - King’s College London, 2018)
In recent years, the South Atlantic has garnered an increased focus for such renewed perils as piracy spikes and transnational drug trafficking flows. In this context, Brazil has attempted to discursively assert its leadership and pre-emptively exclude unwanted interferences from countries and/or organizations that are deemed as not sufficiently in tune with the needs of the Global South. Although deemed less threatening, the European Union (EU) and its state-members are often included in such narrative. This label, however, stands in contrast with the EU’s own latest maritime security efforts in the Gulf of Guinea and capacity-building of several African littoral states. Such a dissociation over a potential North-South fault-line concerning the South Atlantic raises key issues over the bloc’s ability to partake with emerging powers on maritime security issues under both the Strategic Partnerships and Maritime Security Strategy (EUMSS) framework. It also poses new challenges in terms of competing dynamics down South that require holistic and coordinated approaches between every international actor. This paper traces Brazilian interests in the area in juxtaposition to the EU’s own involvement with the region while seeking to unpack the latter’s toolbox to both engage and entice the former towards a more cooperative outcome.